2022
DOI: 10.1038/s41593-022-01109-2
|View full text |Cite
|
Sign up to set email alerts
|

A gradual temporal shift of dopamine responses mirrors the progression of temporal difference error in machine learning

Abstract: It has been proposed that the activity of dopamine neurons approximates temporal difference (TD) prediction error, a teaching signal developed in reinforcement learning, a field of machine learning. However, whether this similarity holds true during learning remains elusive. In particular, some TD learning models predict that the error signal gradually shifts backward in time from reward delivery to a reward-predictive cue, but previous experiments failed to observe such a gradual shift in dopamine activity. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 56 publications
7
70
1
Order By: Relevance
“…In the future, examining the pharmacological manipulation of dopamine D1 receptors is an important step for better circuit-level understanding of the neuronal mechanism of the reward prediction and the reward prediction error. Dopamine neurons in VTA show phasic activity to unexpected reward presentations, but phasic activity to the reward decreases as learning progresses, and the neurons show phasic activity to reward-predictive cues (Amo et al, 2022;Schultz et al, 1997). Thus, in our experiments, increases in pupil size may reflect reward prediction errors in the presentation of the auditory stimulus.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…In the future, examining the pharmacological manipulation of dopamine D1 receptors is an important step for better circuit-level understanding of the neuronal mechanism of the reward prediction and the reward prediction error. Dopamine neurons in VTA show phasic activity to unexpected reward presentations, but phasic activity to the reward decreases as learning progresses, and the neurons show phasic activity to reward-predictive cues (Amo et al, 2022;Schultz et al, 1997). Thus, in our experiments, increases in pupil size may reflect reward prediction errors in the presentation of the auditory stimulus.…”
Section: Resultsmentioning
confidence: 59%
“…However, the neuronal activities of LC neurons in the study of Bouret and Sara (2003) were examined with the reversal of the contingency between the stimulus and the outcome or the re-acquisition after the extinction in the Go/No-Go task. Although the phasic activities to unpredicted reward found in LC neurons (Bouret and Sara, 2004) may be slightly different from those neurons found in dopaminergic neurons found in VTA (Amo et al, 2022;Schultz et al, 1997), both phasic activities of LC and DA neurons are known to show phasic responses to unpredictable events. Moreover, LC neurons show phasic activity in response to a novel stimulus and decreased activity when the stimulus ceases to predict biologically important events (Berridge and Waterhouse, 2003;Vankov et al, 1995).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The state model has a learningrelated temporal shift which leads to rapidly diminished cue-onset prediction errors in the 15 and 30s conditions at 20 trials of training (Figure 5C), in contrast to the data. This occurs due to a moving prediction error that moves backward in time from shock to cue onset over trials (Supplementary Figure 4A-B), a phenomenon which has been recently observed in dopamine neuron responses to appetitive learning (Amo et al, 2022). Such a prediction error can only "arrive" at the cue onset quickly if the distance between cue onset and shock is short.…”
Section: Time Uncertainty Model Matches Learning Effects On Norepinep...mentioning
confidence: 69%